Pengaruh Likuiditas, Profitabilitas dan Ukuran Perusahaan terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Intervening - Farrah Annisya; Diah Nurdiwaty; Mar’atus Solikah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
The food and beverage manufacturing industry in Indonesia continues to show stable growth despite facing post-pandemic economic challenges. However, company values in this sector have fluctuated, indicating the influence of internal company factors. This study aims to analyze the direct and indirect effects of liquidity, profitability, and company size on company value, with financial performance as an intervening or mediating variable. This study uses a quantitative approach with causality research methods to understand the cause-and-effect relationships between variables. The analytical techniques used include path analysis and the Sobel test to test the mediation effect. The results show that profitability has a significant influence on financial performance and also has a direct positive effect on company value. Meanwhile, financial performance has a significant negative effect on company value. Nevertheless, financial performance has been shown to mediate the relationship between profitability and company value. This finding confirms that profitability is a key factor influencing company value, both directly and through financial performance as a mediating variable. Conversely, liquidity and company size were not found to be dominant factors in influencing company value. The practical implication of this study is the importance of focusing on increasing profitability as a primary strategy in corporate financial planning. For investors, these results can also be a consideration in evaluating the health and prospects of a company in making investment decisions.